Do troublesome pupils impact teacher perception of the behaviour of their classmates?. Issue 1 (1st January 2019) - Wienen, Albert W.; Batstra, Laura; Thoutenhoofd, Ernst; Bos, Elisabeth H.; de Jonge, Peter
Abstract: The widely supported wish for more inclusive education places ever greater expectations on teachers' abilities to teach all children, including those with special needs and challenging behaviours. The present study aimed at the question whether teachers judge pupil behaviour more negatively if there are more children with difficult behaviour in class. The teachers of 184 classes in 31 regular primary schools were asked to complete the Strength and Difficulties Questionnaire (SDQ-L) for 3649 pupils. Six linear mixed models were carried out with as independent variable the number of pupils that teachers perceived to have 'abnormal behaviour', and the class mean without these pupils as the dependent variable. For all SDQ-L subscales – emotional problems, behavioural problems, problems with hyperactivity, problems with peers, poor prosocial behaviour and total problems – the number of pupils perceived as problematic was associated with less favourable teacher perceptions of the rest of the class. The results of this study are a plea for a contextual perspective on pupil behaviour in class, both where teachers are asked to report on individual pupils, as well as where interventions are done on emotional and behavioural problems in class.